Hadith #3070 - Sunan Abi Dawud - Muhammad bin Bashar Bindar محمد بن بشار بندار; Umm Jnwb أم جنوب (Sunan Abi Dawud)
Abdullah ibn Hasan al-Anbari said: My grandmothers, Safiyyah and Duhaybah, narrated to me, that hey were the daughters of Ulaybah and were nourished by Qaylah, daughter of Makhramah. She was the grandmother of their father. She reported to them, saying: We came upon the Messenger of Allah (ﷺ). My companion, Hurayth ibn Hassan, came to him as a delegate from Bakr ibn Wa’il. He took the oath of allegiance of Islam for himself and for his people. He then said: Messenger of Allah (ﷺ), write a
Grade: Da'if